Pemodelan dan Verifikasi Formal Pengaruh Mobility pattern Terhadap Handoff Latency pada Jaringan WiMAX - I Nym Saputra Wahyu Wijaya; Reza Pulungan (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
In order to decrease handoff latency and increase the successful of HHO conventional scheme, a development of handover scheme is done in standard protocol WiMAX IEEE 802.16e by adding mobility pattern. The superiority of handover scheme with mobility pattern can reduce handoff latency up to 50%, mean while the weakness of this scheme is a wrong act in determining target base station are often happen. Simulation can not showing the cause of that error. So, we do formal verification in to hard handover model with mobility pattern. In this research, behaviour system is modeled with continuous-time Markov chain (CTMC). The model is foccused to aproximating the influence of mobility pattern in to handoff latency from WiMAX hard handover mechanism. In order to set up a series markov chain models handover system can follow steps, such as: represents the state space, give a number in all transitions, generate the rate transition matrix (infinitesimal generator). Probabilistic model checking in the research are using quantitative properties and qualitative properties. Formal verification concerning properties has relation with handover in WiMAX network showing that 70% from mobile station which doing scanning with mobility pattern are success doing handover. 24% of them doing scanning conventional as a result of wrongness in act determining target base station, so handoff latency which is pictured will bigger than a system that is only use conventional scanning method.